Neurodiversity in the screen industries in Ireland - McSherry, Eleanor (Irish Journal of Arts Management and Cultural Policy, 2024)
Academic and policy discourse have increasingly recognised the significance of diversity around screen industries. To date, there has been insufficient consideration of neurodivergency as a form of disability in the discussions of diversity within the screen industries. In particular, given the range and breadth of neurodiversity as an overarching concept, there needs to be further research on the role of policy interventions to support neurodivergent people accessing work in the screen industries in Ireland. Currently, various media institutions have policies around inclusion, equity and diversity including the British Broadcasting Corporation’s grassroots initiative from 2017, the 50:50 The Equality Project (n.d), British Film Institute ‘BFI Diversity Standards’ (2019), the Raidió Teilifís Éireann ‘Diversity and Inclusion in RTÉ – Reimagined for a New Generation’ (2018) and the UK All Party Parliamentary Group for Creative Diversity (Wreyford et al, 2021). However, none specifically address the lack of neurodivergent people in the screen industries: an issue that adversely impacts the potential of this sector to grow. The lack of working conditions that support this sector adversely impacts the diversity and representation of neurodivergent workers. There is a need to address this current absence of knowledge and policy within the screen industry about neurodiversity and for the industry to become more cognisant of this new neurodiversity movement, as a part of a more diverse reality. People who are neurodivergent are already working in the industry but are possibly afraid to declare their difference. This paper will take an interdisciplinary lens to critically analyse current policy measures to ascertain what is currently being done, or not, in this area of neurodiversity in the screen industry (UK/Ireland) and discuss what the industry needs to do to become more inclusive and more importantly, legally compliant. The aim of this paper is to raise awareness about this growing issue and to start a discourse that might lead to better practices, policies and support for neurodivergent workers in the screen industry. At the end of the article, it offers some possible solutions.